Greenhouse and open-field Tomato farming. A comparison through yield and growth parameters investigated in Dar es Salaam - James Chacha; Murugan Thirumalai; Obeid Idawa; Josephine Chilwea; Concheska Kilamba; Bertha Hussy; Haania Ishaq; Kalidoss Rajendran (Innovations in Agriculture)
Using herbicides is a timesaving technology that could increase crop productivity, revenue, and food security among resource-constrained farmers in the Sub-Saharan Africa (SSA) region. However, the land sizes are small and pose a big question as to whether it is economical to embrace the technology. Again, if not used well, these products could be harmful to humans and other non-targeted organisms that significantly contribute to the well-being of the ecosystem. Across the region, 20 of 45 commonly used active ingredients have LD50 values below 2000 mg/kg. Therefore, proper selection and use of personal protective equipment are necessary to ensure the risks are managed to the lowest level possible. This research presents the current state of herbicide use in the SSA region and the potential health risks that farmers could face. It also outlines potential mitigation strategies that could be adapted for more sustainable usage.